THE FORMATION AND USE OF NOUN IN NOCTE LANGUAGE - Kakali Chutia, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
India is a linguistically diverse country. Due to the migration of many ethnic groups since prehistoric times to India, its language and culture have been developing. Unlike other states of India, The North -East is varied in terms of its linguistic and cultural features which are full of wonders. The North-east comprises of Assam, Arunachal, Nagaland, Mizoram, Manipur, Tripura, Meghalaya and Sikkim. Sikkim has got the recognition of being an indispensable state of NorthEast recently. One of the indispensable states of North-East India is Assam. Assam, that is popularly known as the threshold of North-East is the abode of many ethnic groups. Each group has its own distinguished linguistic and cultural characteristics that make it beautiful. Therefore, sometimes Assam is regarded to be the hub of linguistic assimilation. In Assam, many regional languages are in practices which have its origin from different language family, such as: IndoEuropean, Chinese-Tibetan, Austrick and Dravidian family. One of the languagesthat isin practice in Assam is NOCTE, which decedents from 'Tibbet-Burma'. The NOCTE's live in Tirap district, which is situated in the South-West part of Arunachal Pradesh, is considered as the important Tribe of Nagaorigin. They are rich in their cultural and linguistic identities. They belong to the Mongoloid ethnic group. Apart from Arunachal Pradesh, The Nocte tribes are seen living there in Dihing Kinar Nocte Gaon, situated in Jaypur, Dibrugarh, Paniduwariya gaon (Namrup) and Hiloni Gaon (Sivasagar). Presently, nine dialectal forms are available of Nocte tribes. They are bilingual; they used Nocte as their first language. In this research paper, an attempt has been made to discuss the formation of verbs and its application by the Noctepeople.